The Differences of Mechanisms in Antihypertensive and Anti-Obesity Effects of Eucommia Leaf Extract between Rodents and Humans - Sansei Nishibe; Hirotaka Oikawa; Kumiko Mitsui-Saitoh; Junichi Sakai; Wenping Zhang; Takahiko Fujikawa (Molecules, 2023)
In the 1970s, Eucommia leaf tea, known as Tochu-cha in Japanese, was developed from roasted Eucommia leaves in Japan and is considered as a healthy tea. The antihypertensive, diuretic, anti-stress, insulin resistance improving, and anti-obesity effects of Eucommia leaf extract have been reported. However, the identification and properties of the active components as well as the underlying mechanism of action are largely unknown. In this review, we summarize studies involving the oral administration of geniposidic acid, a major iridoid component of Eucommia leaf extract which increases plasma atrial natriuretic peptide (ANP) on the atria of spontaneously hypertensive rats (SHR) by activating the glucagon-like peptide-1 receptor (GLP-1R). To achieve the antihypertensive effects of the Eucommia leaf extract through ANP secretion in humans, combining a potent cyclic adenosine monophosphate phosphodiesterase (cAMP-PDE) inhibitor, such as pinoresinol di-β-d-glucoside, with geniposidic acid may be necessary. Changes in the gut microbiota are an important aspect involved in the efficacy of asperuloside, another component of the Eucommia leaf extract, which improves obesity and related sequelae, such as insulin resistance and glucose intolerance. There are species differences of mechanisms associated with the antihypertensive and anti-obesity effects between rodents and humans, and not all animal test results are consistent with that of human studies. This review is focused on the mechanisms in antihypertensive and anti-obesity effects of the Eucommia leaf extract and summarizes the differences of mechanisms in their effects on rodents and humans based on our studies and those of others.